La e-accesibilidad y la discapacidad visual en España - Serrano Mascaraque , Esmeralda (Revista General de Información y Documentación, 2009)
The electronic accessibility is one of the aspects related with the disability that it’s acquiring a strong relevancy lately, in consonance with the repercussion of the development and implantation of the TIC and the Information Society are experimenting worldwide in all the aspects of life. In this article we can find the gadgets designed to help that are used based on the type of disability ad statistical data referred to Internet users and the population of Spain that have disability.
Keywords: Web accessibility; Information Society; Disability; Visual handicap; Help tools; Statistical data; Spain